HONORIFICS IN ACTION: A SOCIOLINGUISTIC EXPLORATION OF JAPANESE LANGUAGE USE AMONG INDONESIAN UNIVERSITY STUDENTS - Pujiono, Mhd; Gapur, Abdul; Taulia, Taulia; Azzali, Syafrizal (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This study investigates the use of Japanese honorific language variants (keigo)—teineigo, kenjougo, and sonkeigo—among university students studying Japanese, emphasizing the progression of ability throughout academic levels. The study intends to examine patterns in honorific usage and explore factors affecting students’ application of keigo. A Japanese Literature program was executed utilizing a descriptive qualitative approach and sociolinguistic theory, resulting in data gathering through questionnaires administered to 30 students (10 sophomores, 10 juniors, and 10 seniors). The data indicate that 80% of sophomores utilize teineigo, whereas 40% of juniors employ both sonkeigo and at least 40% of another form. Senior citizens favor sonkeigo and kenjougo due to their extensive cultural-linguistic understanding. Key characteristics encompass formal engagement with elders, maintaining esteemed standards, and readiness for professional settings. These results underscore the imperative for keigo training that is customized to the specific developmental stage of learners, prioritizing pragmatic skill and cultural awareness. The study advocates incorporating sociolinguistic contexts into Japanese language courses to connect classroom instruction with practical communication.